Multi-party semi-quantum private comparison based on the maximally entangled GHZ-type states - Wu, WanQing; Guo, LingNa; Xie, MingZhe (Frontiers in Physics, 2022)
Semi-quantum private comparison (SQPC) aims to use a small amount of quantum capabilities to compare the equality of participants’ secrets. In this paper, TP is a semi-honest third party with all quantum capabilities while the participants’ quantum capability is limited. In recent years, research on semi-quantum privacy comparison protocol has made some achievements, but most of SQPC protocol can only compare the equality of two parties and cannot be extended to the multiparty case. Therefore, we proposed a multi-party semi-quantum private comparison protocol based on the maximally entangled GHZ-type state, which can compare the equality of n parties. What is more, the participant’s encrypted information is not transmitted through the classical channel, which improves the security of the protocol. Finally, the security analysis demonstrates that outside eavesdropper, inside dishonest participant and semi-honest third party cannot obtain any private information.